Irrigation management transfer: The experience of the Río Dulce Irrigation Scheme, Argentina - Salgado, Ramiro (2021)
Many governments and international agencies have promoted irrigation management transfer (IMT) in order to reduce operations and maintenance costs and satisfy farmers' willingness to improve their irrigation service by self‐management. However, IMT has produced both satisfactory and unsatisfactory results. This paper presents a participatory research‐based assessment of IMT in a case study in Northwest Argentina. The study combined conventional irrigation performance assessment and a survey of farmers' perception of the water delivery service and willingness to participate in water users associations. The assessment compared two subsystems in the Río Dulce Irrigation District with different levels of management transfer. Water service in the subsystem where management had been transferred allowed flexible delivery schedules that facilitated a diversified cropping pattern, greater irrigation intensity, and resulted in more water use. Farmers in the transferred subsystem were more aware of the problems of the irrigation service than farmers in the non‐transferred subsystem. The perception of problems in the non‐transferred subsystem increased with the level of the farmer's professionalism and technical knowledge. The transmission of requests and complaints from farmers to managers was more transparent in the transferred subsystem than in the non‐transferred one.